Analisis Pengaruh Kompetensi Bawahan Dan Gaya Kepemimpinan Terhadap Efektivitas Organisasi - Johny, Lesnussa (Fakultas Ekonomi, UIN Maliki Malang, 2010)
This research analyzed some problems, such as: influence of the subordinate competence (X1) and leadership style (X2) toward effectiveness of the organization (Y). Hypothesis of this research is, first, it is presumed that both subordinate competence and leadership style have simultaneously significant influence toward effectiveness of the organization. Second, it is presumed that leadership style has dominant influence toward effectiveness of the organization. Data analysis technique uses multiple regressions. Technique of the sample collecting uses census. Result of the multiple linear regression analysis shows that variables of subordinate competence and leadership style have significant influence toward effectiveness of the organization, therefore, the first hypothesis is accepted. The test result of the regression coefficient value resulted by each independent variable shows that independent variable of leadership style (0.427) has the highest value for the regression coefficient in comparison with the independent variable for the subordinate competence (0.288). The comparison result of the regression coefficient values resulted by each independent variable shows that the second hypothesis is accepted.